Physalin B attenuates liver fibrosis via suppressing LAP2α-HDAC1 mediated deacetylation of GLI1 and hepatic stellate cell activation - Zhu, Xiaoyun; Ye, Shengtao; Yu, Dongke; Zhang, Yanqiu; Li, Jie; Zhang, Meihui; Leng, Yingrong; Yang, Ting; Luo, Jianguang; Chen, Xinlin; Zhang, Hao; Kong, Lingyi (British journal of pharmacology, 2021)
Liver fibrosis is one of the leading causes of morbidity and mortality worldwide of which no acceptable therapy exists. Accumulating evidence supports that glioma-associated oncogene homologue 1 (GLI1) is a potentially important therapeutic target for liver fibrosis. This study investigates the antifibrotic activities and potential mechanisms of Physalin B (PB), a natural Solanaceae compound. Mice subjected to carbon tetrachloride (CCl ) challenge and bile duct ligation (BDL) were used to study the antifibrotic effects of PB in vivo. Mouse primary hepatic stellate cells (pHSCs) and human HSC line LX-2 also served as an in vitro liver fibrosis model. Liver fibrogenic genes, GLI1 and GLI1 downstream genes were examined using western blot and quantitative real-time PCR (qRT-PCR). GLI1 acetylation and LAP2α-HDAC1 interaction were analyzed by coimmunoprecipitation. In animal models, PB administration attenuated hepatic histopathological injury, collagen accumulation, and reduced the expression of fibrogenic genes. PB dose-dependently suppressed fibrotic marker expression in LX-2 cells and mouse pHSCs. Mechanistic studies showed PB inhibited GLI activity in a non-canonical Hedgehog signaling. PB blocked lamina-associated polypeptide 2 α (LAP2α)/histone deacetylase 1 (HDAC1) complex formation thereby inhibited HDAC1mediated GLI1 deacetylation. PB upregulated the acetylation of GLI1, downregulated the expression of GLI1 and subsequently inhibiting HSC activation. PB exerted potent antifibrotic effects in vitro and in vivo by disrupting the LAP2α/HDAC1 complex, increasing GLI1 acetylation and inactivating GLI1. This indicates that PB may be a potential therapeutic candidate for the treatment of liver fibrosis.